Outside : six short stories - Lopez, Barry Holstun, 1945-2020- (Trinity University Press, 2014)
"These six stories offer insight into the relationships between humans and animals, creativity and beauty, and life and death. Barry Moser's eleven layered engravings provide a meditative experience that parallels Lopez's complex sense of our relationship to nature"--"Provided by publisher".